The longitudinal relationship between income and social participation among Chinese older people - Zeyun Feng; Jane Murray Cramm; Chunlin Jin; Jos Twisk; Anna Petra Nieboer (Elsevier, 2020)
The vital role of active social participation in older people's lives is widely acknowledged. The maintenance of adequate levels of social participation is an essential element of successful aging. Low income may inhibit older people from engaging in social activities. Given its recent rapid economic growth, China provides a unique setting for the study of changes in income and social participation among older people over time. In this study, the longitudinal relationship between income and social participation among Chinese older people was investigated using a nationally representative dataset from three waves of the China Health and Retirement Longitudinal Study (CHARLS). At baseline, a total of 3863 participants with a mean age of 60.4 years (range: 50-89) were included in our study; 49.9% of the participants were female, and 64.4% lived in rural areas. Generalized estimating equations were used to analyze the longitudinal relationship between income and social participation, with and without adjustment for background variables (age, gender, marital status, educational level, empty-nest status, area of residence, and multimorbidity). The results of unadjusted and adjusted analyses clearly showed a longitudinal association between income and social participation. People from the highest income group were almost two times more likely to participate in social activities than were those from the lowest income group. People with a higher educational level are also more likely to participate in social activities compared to people with a lower educational level. Being married and living with children decreased the odds of social participation. Social participation is also less likely among older aged and those living in rural areas. Our findings indicate that higher income levels are associated positively with social participation over time among older people in China.